2023
DOI: 10.1111/1750-3841.16601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold storage time on the quality and active probiotics of yogurt fermented by Bifidobacterium lactis and commercial bacteria Danisco

Abstract: In this study, the commercial bacteria Danisco and Bifidobacterium lactis were used to ferment soy yogurt, and then the quality of yogurt and the number of active probiotics in yogurt during storage were investigated. The results showed that the total number of viable bacteria in soy yogurt increased first and then decreased, but all of them met the standard for the number of viable bacteria in probiotic foods. The content of protein, lipid, and total sugar in soy yogurt decreased gradually with the extension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…The survival of probiotics during food storage is critical to the production of probiotic products. As shown in Figure 3(d), the number of LAB initially increased during 0–10 days of storage because LAB can still grow slowly and engage in metabolic activities during the storage period 60 . At 10–20 days of storage, LAB counts declined.…”
Section: Resultsmentioning
confidence: 92%
“…The survival of probiotics during food storage is critical to the production of probiotic products. As shown in Figure 3(d), the number of LAB initially increased during 0–10 days of storage because LAB can still grow slowly and engage in metabolic activities during the storage period 60 . At 10–20 days of storage, LAB counts declined.…”
Section: Resultsmentioning
confidence: 92%
“…Monosaccharide composition analysis showed that F-IDF contained a large amount of glucose, which increased the reducing sugar content in yoghurt, indicating that IDF contains certain polysaccharides and reducing sugars, increasing the nutritional components of yoghurt. During the 21-day storage period, the total sugar and reducing sugar content of different yoghurt groups gradually decreased, as sugar was the main carbon source for microbial growth ( Xu et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the strategies studied by researchers in recent years to increase the growth and survival of probiotics in food products during storage and in the gut after consumption is the use of probiotics and prebiotics in the form of synbiotic products (Kariyawasam et al., 2021 ; Xu et al., 2023 ). Synbiotic products, in which a combination of probiotics and prebiotics are used, improve the survival and selective implantation of useful live microbial strains in the digestive system.…”
Section: Introductionmentioning
confidence: 99%